1994
DOI: 10.1128/mcb.14.3.1544
|View full text |Cite
|
Sign up to set email alerts
|

A new orphan member of the nuclear hormone receptor superfamily that interacts with a subset of retinoic acid response elements.

Abstract: We have identified and characterized a new orphan member of the nuclear hormone receptor superfamily, called MB67, which is predominantly expressed in liver. MB67 binds and transactivates the retinoic acid response elements that control expression of the retinoic acid receptor P2 and alcohol dehydrogenase 3 genes, both of which consist of a direct repeat hexamers related to the consensus AGGTCA, separated by 5 bp. MB67 binds these elements as a heterodimer with the 9-cis-retinoic acid receptor, RXR. However, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
327
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(341 citation statements)
references
References 72 publications
11
327
1
2
Order By: Relevance
“…This could be because PB activation of CAR is not associated with either the activation of a specific p160 coactivator or the translocation of any specific p160 to the nucleus so interaction of CAR with a specific p160 coactivator is not required. Alternatively, although CAR is expressed preferentially in liver, it is also expressed at lower levels in other tissues [25], and it is possible that redundancy of the p160 coactivators permits maximal activation of CAR in tissues that have different relative concentrations of the p160 coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because PB activation of CAR is not associated with either the activation of a specific p160 coactivator or the translocation of any specific p160 to the nucleus so interaction of CAR with a specific p160 coactivator is not required. Alternatively, although CAR is expressed preferentially in liver, it is also expressed at lower levels in other tissues [25], and it is possible that redundancy of the p160 coactivators permits maximal activation of CAR in tissues that have different relative concentrations of the p160 coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PXR (also known as steroid and xenobiotic receptor SXR), CAR heterodimerizes with RXR and binds to the phenobarbital responsive enhancer module (PBREM) to induce the transcription of CYP2B genes (Baes et al 1994;Choi et al 1997;Honkakoski and Negishi 1997). Closer examination of the PBREM and the other CARregulated promoters revealed that CAR preferentially binds to DR4 (direct repeat spaced by 4 nucleotides) binding sites (Honkakoski et al 1998).…”
Section: Nuclear Receptors Car and Pxrmentioning
confidence: 99%
“…With few exceptions, NRs share a common domain based structure comprised of four fundamental domains: A/B domain containing the ligand independent activation function (AF-1), DNA binding domain (designated the C domain), hinge region of lesser defined function (D domain) and the E/F domain containing the ligand dependent activation function (AF-2) as well as the ligand binding domain. The most recent classification scheme for NRs is based on sequence homology in which both the constitutive active/androstane receptor (CAR) and pregnane X receptor (PXR) belong to the NR1I family (NR1I3 and NR1I2, respectively) (Baes et al 1994(Baes et al , 1999. The anti-seizure drugs phenobarbital (PB) and phenytoin are the most well known activators of CAR.…”
Section: Nuclear Receptors Car and Pxrmentioning
confidence: 99%
“…The DBD of RAR and/or RXR binds to the upstream sequences of RA responsive genes in the nucleus [5,7]. RA acts as a ligand to activate transcription of target genes by the binding of RAR/ RXR as a dimer to the specific sequences of DNA called retinoic acid response elements (RARE) [3,7,12].…”
Section: Introductionmentioning
confidence: 99%
“…spacer as the DR-5 or it contains a direct repeat of TGACCT (complementary sequence of AGGTCA) with a spacer of 5 bp as in the reverse orientation [3,5,7,12] (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%